Perancangan Sistem Point of Sale Berbasis Web Menggunakan Framework CodeIgniter: Studi Kasus Toko Agen Satria - Zahra, Nabila; Tukino, Tukino; Priyatna, Bayu; Hilabi, Shofa Shofia (STMIK Banjarbaru, 2025)
The Satria Agent Store still carries out transactions and manages goods data manually, causing the risk of errors, delays and difficulties in checking sales reports. This condition hampers operational efficiency and is not in accordance with developments in information technology. This research aims to develop a web-based Point of Sale (POS) system to support store operations. The system was developed using the CodeIgniter framework with MVC architecture, use of the PHP language, and MySQL as the database. The development method uses the Waterfall model which includes requirements analysis, system design, implementation and testing. The resulting system is able to support transactions, goods management and real-time sales reports. Testing using Black Box Testing ensures that the function runs according to plan, while the System Usability Scale (SUS) gives a score of 73.22, indicating the system is in the “good” category. This system is expected to increase the efficiency and operational efficiency of the Satria Agent Store.Keywords: Point of Sale; Website; CodeIgniter; Waterfalls AbstrakToko Agen Satria masih melakukan transaksi dan pengelolaan data barang secara manual, menyebabkan risiko kesalahan, keterlambatan, dan kesulitan pengecekan laporan penjualan. Kondisi ini menghambat efisiensi operasional dan tidak sesuai dengan perkembangan teknologi informasi. Penelitian ini bertujuan mengembangkan sistem Point of Sale (POS) berbasis web untuk mendukung operasional toko. Sistem dikembangkan menggunakan framework CodeIgniter dengan arsitektur MVC, penggunaan bahasa PHP, dan MySQL sebagai basis data. Metode pengembangan menggunakan model Waterfall yang meliputi analisis kebutuhan, perancangan sistem, implementasi, dan pengujian. Sistem yang dihasilkan mampu mendukung transaksi, pengelolaan barang, dan laporan penjualan secara real-time. Pengujian menggunakan Black Box Testing memastikan fungsi berjalan sesuai rencana, sedangkan System Usability Scale (SUS) memberikan skor 73,22, menandakan sistem memiliki kategori Good. Sistem ini diharapkan meningkatkan efisiensi dan efisiensi operasional Toko Agen Satria.